Pengaruh Kualitas Produk dan Word of Mouth terhadap Niat Membeli Kembali dengan Keputusan Pembelian sebagai Mediasi Dalam Menggunakan Maxim - Muriati Muriati; Rino Rino (Universitas Negeri Padang, 2022)
This research aims.to examines the effect of product quality and word of mouth on repurchase interest and purchase decisions as mediate variables on Universitas Negeri Padang Students using Maxim application. This research conducted by quantitative (causal) method. Purposive sampling and Cochran formulation were use in this research. Total sample was 97 respondents. This research used primary data with spreading questionnaire to students at Universitas Negeri Padang who had using Maxim apps. SEM PLS 3.0 analysis also used in this research. SEM PLS analysis showed that : 1) Product quality didn’t have any significant impact on repurchase interest. 2) Word of Mouth had a significant impact on repurchase interest. 3) Product quality had a significant impac on purchase decisions. 4) Word of Mouth had a significant impact on purchase decisions. 5) Purchase decisions had a significant impact on repurchase interest. 6) Product quality gave a significant impact on repurchase interest mediated by purchase decisions. 7) Word of Mouth didn’t have any significant impact on repurchase interest mediated by purchase decisions. Keywords : product quality, word of mouth, purchase decisions, repurchase interest